Switching of the redox centers of a tris-2-mercaptophenolato chromium(iii) metalloligand by a guest metal ion. Issue 6 (26th January 2023) - Wakizaka, Masanori; Matsumoto, Takeshi; Chang, Ho-Chol
Abstract : This work demonstrated the S-site binding tri-nuclear structure using a tris-type 2-mercaptophenolato metalloligand and switching of the redox centers. Abstract : This work reports that the redox-active metalloligand (ML) fac -[Cr III (mp)3 ] 3− (mp: 2-mercaptophenolato) coordinates with a Co(iii ) ion to afford the trianionic complex [Co III { fac -Cr III (mp)3 }2 ] 3− . The free ML shows ligand-centered redox processes, whereas the guest-metal-bound trinuclear structure exhibited a guest-metal-centered Co(ii )/Co(iii ) redox couple, demonstrating redox switching through guest-metal binding to the MLs.